Semen quality in papaya workers with long term exposure to ethylene dibromide. - Ratcliffe, J M (1987)
To examine whether long term occupational exposure to ethylene dibromide (EDB) affects semen quality a cross sectional study of semen quality was conducted among 46 men employed in the papaya fumigation industry in Hawaii, with an average duration of exposure of five years and a geometric mean breathing zone exposure to airborne EDB of 88 ppb (eight hour time weighted average) and peak exposures of up to 262 ppb. The comparison group consisted of 43 unexposed men from a nearby sugar refinery. Statistically significant decreases in sperm count per ejaculate, the percentage of viable and motile sperm, and increases in the proportion of sperm with specific morphological abnormalities (tapered heads, absent heads, and abnormal tails) were observed among exposed men by comparison with controls after consideration of smoking, caffeine and alcohol consumption, subject's age, abstinence, history of urogenital disorders, and other potentially confounding variables. No effect of exposure to EDB on sperm velocity, the overall proportion of sperm with normal morphology, or YFF bodies was observed. These data strongly suggest that EDB may increase the risk of reproductive impairment in workers at exposure levels near the National Institute for Occupational Safety and Health recommended limit of 45 ppb (as an eight hour time weighted average) and far below the current standard of the Occupational Safety and Health Administration of 20 ppm.